Listening to the women’s experience of perinatal domestic violence during the COVID-19 pandemic: a qualitative content analysis - Raheleh Babazadeh; Malikeh Amel Barez (BMC Pregnancy and Childbirth)
Abstract Background Pregnant women and their fetuses would be a high-risk population and more susceptible to COVID-19 infection. Since the outbreak of COVID-19, quarantine, social distancing and isolation, and the consequences were likely to increase the risk of domestic violence dramatically. This study aimed to explore women’s experiences of perinatal domestic violence during the COVID-19 pandemic. Methods This qualitative study was conducted from November 2020 to December 2022 in Mashhad, Iran. Data were collected through remote individual semi-structured interviews with 9 women who experienced perinatal domestic violence, and 7 key informants with relevant specialists, until data saturation was achieved. The data were analysed using conventional content analysis, as adopted by Graneheim and Lundman. Results The 4 main themes that emerged from the data analysis were “aggravators of perinatal violence”, “enhanced vulnerability”, “strategies for dealing with perinatal violence” and “neglected needs”. Conclusion The high prevalence and the adverse consequences of perinatal domestic violence during the COVID-19 crisis provide a golden opportunity for performing appropriate interventions. The perinatal period provides a crucial opportunity to identify and support pregnant women who have been victimized and may have lost contact with other supportive services during the COVID-19 pandemic. Psychological and physical support, as well as social connectedness, are important strategies during the period of isolation for individuals at risk of domestic violence during the COVID-19 pandemic.